The practice of parresia by nurses in caring for women in situations of domestic violence (Research, Society and Development, 2020)
Objective: to identify the practice of parresia, by primary care nurses, in caring for women in situations of domestic violence. Method: qualitative, descriptive study. Data were collected between April and June 2018 through semi-structured interviews. They were inserted in the NVivo Software, treated in the light of Textual Discursive Analysis and based on Foucault's philosophical thinking. Results: four analytical categories were formed: the exercise of parresia in the face of occult violence, the exercise of parresia in the face of corporate violence, the exercise of parresia in the presence of the aggressor and the exercise of parresia and the interfering factors. Final considerations: primary care nurses, even with difficulties, exercise parresia in the care of women in situations of violence, speaking the truth of what is thought and known about this problem. The welcoming dialogue with women about the interfaces of violence, the sharing of clear and concise information about the support network are actions that characterize the exercise of parresia by nurses.